The education trap schools and the remaking of inequality in Boston - Groeger, Cristina Viviana, 1986- (Harvard University Press, 2021)
"For generations, Americans have looked to education as the solution to economic disadvantage. Yet, although more people are earning degrees, the gap between rich and poor is widening. Cristina Groeger delves into the history of this seeming contradiction, explaining how education came to be seen as a panacea even as it paved the way for deepening inequality."--